Optimising care of patients with chronic disease: patient‐oriented education may improve disease knowledge and self‐management. Issue 8 (August 2017) - Hayward, Kelly L.; Horsfall, Leigh U.; Ruffin, Brittany J.; Cottrell, W. Neil; Chachay, Veronique S.; Irvine, Katharine M.; Martin, Jennifer H.; Powell, Elizabeth E.; Valery, Patricia C.
Abstract: Many patients with chronic disease do not possess the knowledge and skills required to access and interpret appropriate health information. A pilot study in people with liver cirrhosis ( n = 50) identified that only 54% of patients could recall being given written information by a clinician and 64% had self‐sought information, most commonly using the Internet. Many patients reported difficulties understanding the material and the majority wanted more accessible information. A pilot chronic disease educational booklet was well received by the study participants with 85% reporting it was helpful and 78% using it in between clinic appointments.